EPCSAC - Extensible Platform for Cloud Scheduling Algorithm Comparison - Toledo Junior, Tiago José; Bruschi, Sarita (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2020)
When developing a new cloud scheduling algorithm, simulation is the most used approach to test the algorithm, mainly due to the impossibility of controlling all the cloud variables and also because of the costs involved. However, setting up the simulation environment can be a difﬁcult task and each environment can be conﬁgured its own way, resulting in no easy way of reproducing the results with other published algorithms neither comparing both under the same circumstances. To solve both of these problems, we propose the EPCSAC, an online open-source platform that allows researchers to worry only about the creation of their algorithm. They are able to create a set of simulation parameters, test their algorithm under these parameters, and compare their results with other algorithms on the platform. This way, there is an improved reproducibility and a reduced overhead of development. Researchers may have access to the platform at epcsac.lasdpc.icmc.usp.br/.